PROFIL PENDIDIKAN PANCASILA SEBAGAI UPAYA MEMBENTUK KARAKTER PELAJAR PANCASILA DI ERA METAVERSE - Istianah Istianah; Makarius Erwin Bria; Marsi D.S Bani (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2022)
The development of digitalization is changing faster. The world is now faced with a transition from analog to digitalization. In 2021, the world community will be shocked by the metaverse era that is increasingly accelerating the digitization of human life. The impact of advances in science and technology can be positive and negative. Conical on the negative side, it can be seen in the pattern of human life and behavior that deviates from values, norms, and morals. Pancasila education is part of the personality development course in national education in Indonesia. Pancasila Student Character is a character that is expected to be formed through Pancasila Education which is applied in Higher Education. Students who have this profile are students who are fully developed through the 6 (six) dimensions of their formation. These dimensions include: 1) Faith, fear of God Almighty and have noble character; 2) Independent; 3) Working together; 4) Global diversity; 5) Critical reasoning; 6) Creative. The purpose of writing This article was written with the aim of knowing the Profile of Pancasila Education as an effort to shape the character of Pancasila students in the Metaverse Era. This research is a type of library research or literature study, which seeks theoretical references related to cases or problems found. The author uses descriptive analysis method to analyze the data obtained. Pancasila education is an effort to shape the character of Pancasila students in the metaverse era by developing Indonesian cultural values and Pancasila which is the foundation of national development. Efforts to create the character of Pancasila Students are not only a movement in the education system, but also a community movement. Naming the Pancasila Student Profile aims to strengthen the noble values of Pancasila in each individual student. Pancasila is the most appropriate word to summarize all the characters and competencies that are expected to be possessed by every Indonesian student.